Governance for a Sustainable Future
VIII, 364 p. 25 illus., 12 illus. in color.
Keywords: Although the expression “responsibility to future generations” is firmly established in public and political vocabulary, its operational meaning and practice are inadequately understood and yet to be systematically evaluated. Moreover, the term has not been successfully translated into viable ethical and theoretical concepts that can guide public policies and actions. How can the modes of governance and established policy priorities become compatible with the well-being of future generations? The primary objective of this book is to identify the conditions of and obstacles to governance for a sustainable future, or future-regarding governance. Governance concerns steering a society over extended periods of time, not responding to particular policy issues. The ideas and strategies proposed by contributors in this book to establish future-regarding governance are based on the theoretical and empirical analyses of the major long-term problems facing advanced democracies in general, and Japan in particular. Japan is an interesting case indeed. Relatively poor climate policy, rapidly decreasing birth rate, aging population, extensive public debt, prolonged economic recession, healthcare and pension systems that urgently require redesigning, hollowing-out of industries and subsequent loss of jobs, deteriorating infrastructures, increasing nuclear waste, and intensifying social polarization have caused a decline in people’s trust in the government and democratic processes. Currently, Japanese citizens are widely circulating their doubts about the social system’s sustainability. This book comprises two parts. In Part I, authors from various disciplinary backgrounds examine the idea of governance for a sustainable future from theoretical perspectives. This part discusses issues associated with future-regarding governance that are wicked in nature, such as the philosophical/ethical foundation on which to base the idea of governance for a sustainable future, major impediments to the development of future-regarding governance, and the modes of thinking and action required by leaders and citizens to realize such governance. Chapters in Part II largely focus on the state of long-term governance in Japan. This part uses empirical and in-depth analyses with cross-sectoral and cross-national policy perspectives to identify the state of future-regarding governance in various policy fields and major sectors or organizations mainly in Japan, while also examining strategies and measures to improve their performance. From this perspective, Western democracies and weak democratic regimes elsewhere will be provided with valuable lessons to avoid fatal policy mistakes, thereby improving future-oriented governance worldwide. By combining theoretical discussions on far-reaching issues and empirical analyses of Japanese cases, the book will shed a new light on governance for a sustainable future.